MANAJEMEN DAKWAH DI DALAM ERA SOCIETY 5.0 - Shofiyullahul, Kahfi; Vita, Zuliana (Department of Da'wah Management, Faculty of Da'wah, IAINU Tuban, 2022)
Abstract: Digital da'wah is the answer to the changing times of the digitalist era. Digital da'wah is also a forum for innovation in delivering appropriate Islamic studies in the face of an era revolution that is growing rapidly, such as the industrial revolution 4.0 towards society 5.0. The purpose of the research is to describe the methods and media of da'wah that are appropriate to be applied to the current era. Methodologically, this research uses a qualitative approach, literature study method, to describe da'wah breakthroughs through digital media that has developed widely. This study is expected to provide knowledge to all components of society in developing Islamic studies, not sticking to the theory but the right method to meet the times.